2008
DOI: 10.1192/bjp.bp.108.050088
|View full text |Cite
|
Sign up to set email alerts
|

Extrapyramidal side-effects of antipsychotics in a randomised trial

Abstract: The incidence of treatment-emergent EPS and change in EPS ratings indicated that there are no significant differences between second-generation antipsychotics and perphenazine or between second-generation antipsychotics in people with schizophrenia.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
149
5
3

Year Published

2011
2011
2018
2018

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 231 publications
(168 citation statements)
references
References 50 publications
6
149
5
3
Order By: Relevance
“…Similar to our study, from a population that consisted a large proportion of previously used first generation antipsychotics, Woods (29) reported classical and atypical antipsychotics, contrary to popular belief, were not different in terms of TD risk.…”
Section: Discussionsupporting
confidence: 72%
“…Similar to our study, from a population that consisted a large proportion of previously used first generation antipsychotics, Woods (29) reported classical and atypical antipsychotics, contrary to popular belief, were not different in terms of TD risk.…”
Section: Discussionsupporting
confidence: 72%
“…In a recent review of 12 trials published between 2004 and 2008, the annual incidence of TD was found to be 3.9 % for SGAs and 5.5 % for first-generation drugs [36]. Several other studies have found no change in the incidence at all [38][39][40].…”
Section: Is Td Disappearing?mentioning
confidence: 99%
“…Moreover, results in favor of SGAs have not been uniform, with at least two adult studies failing to find an advantage for SGAs (de Leon, 2007;Miller et al, 2008).…”
Section: Introductionmentioning
confidence: 99%
“…However, the actual evidence for a low TD risk of SGAs is still limited, and, recently, advantages of SGAs vs firstgeneration antipsychotics (FGAs) regarding TD prevalence (de Leon, 2007) and incidence rates (Miller et al, 2008;Lee et al, 2005) have been questioned. Two recent systematic reviews pooled data on prevalence (Davidson et al, 2000) and incidence rates (Correll and Schenk, 2008;Correll et al, 2004) of TD or dyskinesia from studies using SGAs and FGAs that lasted at least 1 year.…”
Section: Introductionmentioning
confidence: 99%